OLIY TA’LIMDA TALABALARNI BAHOLASH TIZIMINI QAT’IYMAS YONDASHUV ASOSIDA TAKOMILLASHTIRISH - Bazarbaeva, A.K. (SCIENCE and SOCIETY, 2022)
This article discusses the issues of improving the student assessment system in higher educational institutions based on the fuzzy mathematic approach. At the level of students' knowledge, methods for solving problems are given based on membership functions of an indefinite set describing the values of linguistic variables.
Keywords: education; quality; fuzzy mathematical modeling; pedagogy; evaluation; expert; intellectual; function; objects